A mutant of Azospirillum brasilense Sp7 impaired in flocculation with a modified colonization pattern and superior nitrogen fixation in association with wheat. - Katupitiya, S (1995)
We report here significant phenotypic and genetic differences between Azospirillum brasilense Sp7 and spontaneous mutant Sp7-S and their related properties in association with wheat. In contrast to the wild-type strain of Sp7, colonies of Sp7-S stained weakly with Congo red when grown on agar media containing the dye and did not flocculate in the presence of fructose and nitrate. Scanning and transmission electron micrographs showed clearly that the Sp7-S strain lacked surface materials present as a thick layer on the surface of the wild-type Sp7 strain. Different patterns of colonization on wheat roots between Sp7 and Sp7-S, revealed by in situ studies using nifA-lacZ as a reporter gene, were related to a large increase in nitrogenase activity (acetylene reduction) with Sp7-S in association with normal and 2,4-dichlorophenoxyacetic acid-treated wheat for assays conducted under conditions in which the nitrogenase activity of free-living Azospirillum organisms was inhibited by an excess of oxygen. Randomly amplified polymorphic DNA analysis indicated the close genetic relationship of Sp7-S to several other sources of Sp7, by comparison to other recognized strains of A. brasilense. Genetic complementation of Sp7-S was achieved with a 9.4-kb fragment of DNA cloned from wild-type Sp7, restoring Congo red staining and flocculation.